Formação docente, educação ambiental e representações sociais: uma pesquisa com três professores(as) especialistas em educação ambiental - Araujo, Lila Maria Malcorra (2007)
This research has origin from two factors: the professional concern with the routes of the Environmental Education concerning school institutions and, a certain discomfort in being a teacher, generated for the (mis)understanding, on the part of the society in general, of conceptual aspects embraced by this field of knowledge. These factors had been proved throughout my pedagogical experience as an educator in the Municipal Net of Education in Santa Maria and as a Pedagogical Supervisor of elementary school (Final Series) of this net. I understand the school as a privileged place for discussion about the social problems, amongst which I point out the Environmental Education as well as the role of raising some representations, being pointed as alternative forms to reconcile practical discourses related to this theme. From this brief contextualization, I proposed to identify and to analyze some representations on Environmental Education of three teachers, who are specialists in Environmental Education and work in the Municipal Public Net of Education in Santa Maria. In order to carry out this research I made use of the Theory of the Social Representations as a point of departure for my analyses of moscoviciana orientation. Three teachers specialists in Environmental Education were interviewed while acting in classroom: the first one in the Child Education, the second one in elementary school (Initial Series) and a third one in elementary school (Final Series). In the first phase of the research a quali-quantitative survey was carried out concerning the initial formation of the teachers who have taken Course of Specialization in Environmental Education in professional exercise. In the second phase, interviews half-structuralized had been carried out with the teachers. In the analyses of the teacher s talks I used the Technique of the Analysis of Content that made possible the identification and attribution of sensible and meaning to certain excerpts of the interviews with the professors. The methodological decision for a qualitative analysis of talks, through the Theory of the Social Representations, as well as the choice of meaningful excerpts, have made possible to identify the representations on ecological questions even if presented very often scarcely in the talks regarding the characteristics of the analyzed material, as well as of the subject that I proposed to investigate: the environmental thematic in the school context. I emphasize the significant number of teachers that act in the education nets who have struggled to extend their initial qualifications through specialization courses, in which the research subject is the Environmental Education. The importance of the specialization courses for the collaborating teachers of this research is crucial for their personal and professional growth, and besides that, studying more makes the teachers more involved with the environmental thematic concerning school space. The Environmental Education has been displayed as a challenge for the teachers involved with it. One of the greatest contributions in this sense has been the fact that they realized that they have to work together as a group.